2014
DOI: 10.1098/rsob.130202
|View full text |Cite
|
Sign up to set email alerts
|

A novelO-linked glycan modulatesCampylobacter jejunimajor outer membrane protein-mediated adhesion to human histo-blood group antigens and chicken colonization

Abstract: Campylobacter jejuni is an important cause of human foodborne gastroenteritis; strategies to prevent infection are hampered by a poor understanding of the complex interactions between host and pathogen. Previous work showed that C. jejuni could bind human histo-blood group antigens (BgAgs) in vitro and that BgAgs could inhibit the binding of C. jejuni to human intestinal mucosa ex vivo. Here, the major flagella subunit protein (FlaA) and the major outer membrane protein (MOMP) were identified as BgAg-binding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 72 publications
2
50
0
1
Order By: Relevance
“…The exact function of PEB3 remains to be determined (Min et al, 2009; Rangarajan et al, 2007). Recently, the major outer membrane protein MOMP in C. jejuni was shown to be O-glycosylated, and the glycosylation is important for binding human histo-blood group antigens and biofilm formation (Mahdavi et al, 2014). It is anticipated that more O-glycosylated surface proteins will be discovered because of advanced analytic glycan detection tools and the presence of a general O-linked glycosylation machinery in C. jejuni .…”
Section: Surface Protein Glycosylation In Bacteria Found In the Gut Mmentioning
confidence: 99%
“…The exact function of PEB3 remains to be determined (Min et al, 2009; Rangarajan et al, 2007). Recently, the major outer membrane protein MOMP in C. jejuni was shown to be O-glycosylated, and the glycosylation is important for binding human histo-blood group antigens and biofilm formation (Mahdavi et al, 2014). It is anticipated that more O-glycosylated surface proteins will be discovered because of advanced analytic glycan detection tools and the presence of a general O-linked glycosylation machinery in C. jejuni .…”
Section: Surface Protein Glycosylation In Bacteria Found In the Gut Mmentioning
confidence: 99%
“…Instead, the transcriptional regulator ToxR, which modulates expression of the outer-membrane proteins OmpU and OmpT in V. cholerae, was found to be necessary for the survival of this pathogen within amoebae (Valeru et al, 2012), but no potential orthologues of these proteins could be found in C. jejuni. However, K. pneumoniae outer-membrane protein OmpA, important for the resistance to phagocytosis by the amoeba Dictyostelium discoideum (March et al, 2013), shares the highest similarity with C. jejuni CadF. In addition to OmpA, the outer-membrane protein OmpK36 and LPS of K. pneumoniae were also found to be important for the resistance to phagocytosis.…”
Section: Jejuni Interaction With Tissue Culture Host Cellsmentioning
confidence: 99%
“…In addition to OmpA, the outer-membrane protein OmpK36 and LPS of K. pneumoniae were also found to be important for the resistance to phagocytosis. Although no OmpK36 orthologues could be found in C. jejuni, the latter does produce a porin protein (PorA, also known as the major outer-membrane protein, MOMP), which was shown to be important for bacterial attachment to epithelial cells (Moser et al, 1997;Mahdavi et al, 2014). Moreover, the L. pneumophila outer-membrane efflux protein TolC, which plays a role in multidrug resistance, and is important for the organism's virulence, invasion and intracellular multiplication inside amoebae (Ferhat et al, 2009), shares sequence and functional similarity with the C. jejuni multidrug efflux pump protein CmeC.…”
Section: Jejuni Interaction With Tissue Culture Host Cellsmentioning
confidence: 99%
“…How these minor changes lead to a major change in virulence is intriguing, but it is probably due to alteration of a key function of MOMP, which has been identified as a porin and adhesion (20)(21)(22). Additionally, glycan modification of MOMP was previously shown to be involved in intestinal colonization (20). However, these previously known functions of MOMP may not fully explain its key role in causing abortion and it is highly possible that MOMP has a yet-tobe-discovered role in mediating pathogen-host interaction and enabling systemic infection.…”
Section: Design Of a Directed Genome Evolution Strategy For Identifyingmentioning
confidence: 99%
“…porA encodes the MOMP in C. jejuni and MOMP has been shown to function as a porin and adhesion (20)(21)(22). MOMP is the most abundant membrane protein in C. jejuni with 18 β-strands and nine external loops (23).…”
Section: Design Of a Directed Genome Evolution Strategy For Identifyingmentioning
confidence: 99%